Expression of TRPM6 and TRPM7 in the preterm piglet heart - Forbes, Elizabeth M.; Bakrania, Bhavisha A.; Steane, Sarah E.; Moritz, Karen M.; Lingwood, Barbara E.; Eiby, Yvonne A. (Frontiers in Pediatrics, 2022)
Preterm infants are at increased risk of death and disability, and cardiovascular instability after birth is a contributing factor. Immaturity of calcium handling in the preterm heart may limit myocardial contractility and cardiac output. Two transmembrane cation channels, TRPM6 and TRPM7, may regulate intracellular cardiac calcium in the neonatal period. The aim of this study was to determine TRPM6 and TRPM7 mRNA expression in piglet hearts in late gestation, and the effects of sex, maternal glucocorticoids, and the transition to extrauterine life. Left and right ventricular tissue was collected from caesarean delivered piglets at birth (91d, 97d, 100d, 113d of gestation; full term 115d), at 6h old (97d, 113d), following maternal glucocorticoid treatment (91d, 97d), and from spontaneously born term piglets at 12-24h old. TRPM6 and TRPM7 mRNA expression was measured using RT qPCR. Males had significantly lower TRPM7 expression in the left ventricle across all gestational ages compared to females. At term, both ventricles had higher TRPM7 expression at 6h old than at birth. In preterm piglets, TRPM7 expression only increased postnatally in the right ventricle following maternal glucocorticoid exposure. At 12-24h old, TRPM7 expression in both ventricles was lower than levels in 6h old term Caesar piglets (113d). Male preterm piglets may have immature myocardial Ca2+ handling and this could contribute to their poorer outcomes. Increased TRPM7 expression is the mature response to birth that is missing in preterm neonates. TRPM7 could serve as a novel target to improve cardiac function in preterm neonates.